PENGARUH TRANSFORMATIONAL LEADERSHIP DAN ORGANIZATIONAL RISK CULTURE TERHADAP EMPLOYEE COMPLIANCE BEHAVIOR MELALUI INTERNAL CONTROL AWARENESS PADA SEKTOR PUBLIK - Zakky Chaidar; Osly Usman (JURNAL LENTERA BISNIS, 2026)
This research investigates the impact of transformational leadership and the organizational risk culture on the compliance behavior of employees, mediated by their awareness of internal controls within the public sector. The primary concern addressed is the imperative to enhance employee compliance to bolster accountability, integrity, and the efficacy of internal controls in public institutions. This scholarly endeavor employs a quantitative explanatory research design. Empirical data were gathered through an online survey utilizing a Likert-scale questionnaire, which included responses from 124 employees within the public sector. The data were subjected to analysis via Partial Least Squares-Structural Equation Modeling using SmartPLS 4. The findings reveal that transformational leadership exerts a positive and statistically significant influence on internal control awareness (β = 0.289; p = 0.002) as well as on employee compliance behavior (β = 0.306; p = 0.001). Furthermore, organizational risk culture demonstrates a positive and significant effect on internal control awareness (β = 0.357; p < 0.001), although its direct impact on employee compliance behavior is not statistically significant (β = 0.082; p = 0.334). Awareness of internal controls is shown to have a positive and significant effect on employee compliance behavior (β = 0.472; p < 0.001). Additionally, internal control awareness mediates the relationships between transformational leadership and organizational risk culture and employee compliance behavior. The results suggest that compliance within the public sector can be effectively enhanced through the mechanisms of leadership, risk culture, and heightened awareness of internal controls.